Effect of Omega-3 Polyunsaturated Fatty Acid on the Prevention of Atrial Fibrillation after Off-Pump Coronary Artery Bypass Grafting - Rakibuzzaman, AKM; Sazzad, Faizus; Wadud, Mohammad Armane; Gafur, Md Abdul; Islam, Shahnaz; Jahan, Israt; Khan, Md Azizul Islam; Sarker, Rampada (University Heart Journal, 2022)
Background: Postoperative atrial fibrillation (POAF) often occurs in patients after coronary artery bypass graft surgery (CABG), both conventional and off pump ranges from 11% to 40%. Although often transient, self-limited, and benign, it may be associated with increased postoperative morbidity. The prevention of POAF has been associated with improved postoperative outcomes in terms of reduced medical treatment, laboratory tests, shorter nursing time, and hospital stay, even when uncomplicated. The present study was conducted to find out the effect of omega polyunsaturated fatty acid on the prevention of POAF after off pump CABG. Method: This cross-sectional study was conducted in the Department of Cardiac Surgery, National Institute of Cardiovascular Diseases (NICVD), Sher-E-Bangla Nagar, Dhaka, between September 2017 and August 2018. Total 100 patients with sinus rhythm admitted for OPCAB were included in this study, and they were divided into two groups, Group A, 50 patients having omega-3 PUFA in the preoperative and postoperative period up to the fifth postoperative day (POD) and Group B, 50 patients not having omega-3 PUFA in the preoperative and postoperative period up to the fifth POD. Findings were compared between two groups preoperatively, postoperatively, up to 5 days, at discharge, and at one month after discharge. Results: Postoperative AF was significantly higher in group B in comparison to group A up to 5th POD. AF was present in a few patients during discharge and one month after discharge, but the differences were statistically not significant between groups. Total ICU stay was similar between the two groups, but the postoperative hospital stay was shorter in Group A, and the mean difference was statistically significant. Conclusion: This study concluded that perioperative oral omega-3 polyunsaturated fatty acid intake reduces the incidence of postoperative atrial fibrillation in patients undergoing off pump coronary artery bypass graft surgery. University Heart Journal 2022; 18(1): 36-43